Effect of Corn Steep Liquor on Bamboo Biochemical Pulping Using Phanerochaete chrysosporium - Faizatul Falah; Widya Fatrisari; Riksfardini A Ermawar; Dedi TA Nugroho; Euis Hermiati (Masyarakat Peneliti Kayu Indonesia, 2011)
The effect of corn steep liquor (CSL) loading on white rot fungi inoculums in the biochemical pulping of betung bamboo was investigated. The best condition of the pretreatment was also determined. There were two conditions of CSL amount used i.e. 1% (v/w) and 10 % (v/w) of CSL used in 100 ml of inoculums. In short, fresh bamboo chips without bark was incubated with Phanaerochaete chrysosporium inoculum stocks for 30 and 45 days at room temperature and followed by Kraft and Soda pulpings. SEM images of pretreated chips were taken after incubation. The pulp yield, Kappa number, freeness, delignification selectivity, and brightness were analyzed. The more CSL amount added with Kraft process gave better results on pulp yield. Increasing incubation time increased pulp yields and decreased the Kappa numbers. On the other hand, freeness and brightness of pulp increased especially for Kraft process. The SEM images showed that there were cell walls degradation activities. The best properties of pulp were obtained by the Kraft process for the treatment of 10% CSL with 30 days of incubation time.Key words: betung bamboo, biochemical pulping, corn steep liquor, Phanaerochaete chrysosporium